2023
DOI: 10.3390/jcm12072502
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth Restriction Is Associated with Pregnancy Associated Plasma Protein A and Uterine Artery Doppler in First Trimester

Abstract: Fetal growth restriction (FGR) is a major cause of stillbirth and poor neurodevelopmental outcomes. The early prediction may be important to establish treatment options and improve neonatal outcomes. The aim of this study was to assess the association of parameters used in first-trimester screening, uterine artery Doppler pulsatility index and the development of FGR. In this retrospective cohort study, 1930 singleton pregnancies prenatally diagnosed with an estimated fetal weight under the third percentile wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…In this study, the FGR and control groups exhibited changing trends in the sFlt-1/PlGF ratio, so this variable was not included (Figure S7). Previous research has shown that low levels of PAPP-A are associated not only with an increased risk of chromosomal abnormality but also an increased risk of low birth weight 34 . Although the univariate analysis showed that PAPP-A level differed significantly between the FGR and control groups, it was not selected for inclusion in the final model by lasso regression.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the FGR and control groups exhibited changing trends in the sFlt-1/PlGF ratio, so this variable was not included (Figure S7). Previous research has shown that low levels of PAPP-A are associated not only with an increased risk of chromosomal abnormality but also an increased risk of low birth weight 34 . Although the univariate analysis showed that PAPP-A level differed significantly between the FGR and control groups, it was not selected for inclusion in the final model by lasso regression.…”
Section: Discussionmentioning
confidence: 99%